Customer relationship management practices in the online community - Wikipedia. (2016) - Alavi, Shirin
Wikipedia is multilingual and the largest open content website which depends on its users to produce information of value. Wikis are often used to create and power collaborative and community websites. The Wikipedia has over 5 million registered users and over 24 million articles out of which 4.1 million in English alone are written by volunteers around the world. Wiki articles can be edited by anyone who has access to them. The issue of who does the work in Wikipedia the few or the masses has been a subject of debate for quite long. This paper aims to analyse the Wikipedia virtual community, which is devoted to the creation of a free encyclopaedia. The key findings indicate that a small proportion of editors account for most of the work done and the value produced. The community dynamics of Wikipedia has been discussed, a conceptual model is proposed and further the CRM strategies have been formulated to attract, retain and engage editors in the Wikipedia Community. The right content developed in the Wikipedia Community would further be a good source for both academia and industry research purposes.